The use, meaning and functions of Slovene bare pronouns - Gregorčič, Kristina (Slovenski jezik, 2024)
The paper presents selected aspects of the use and meaning of Slovene bare pronouns. An extensive quantitative and qualitative analysis of concordances from the reference corpus Gigafida 2.0 allows for a new, more accurate classification of these pronouns in terms of their indefinite pronoun functions (Haspelmath 1997), as well as their cate-gorization as epistemic indefinite pronouns and Negative Polarity Items. Furthermore, the corpus data show that the placement of barepronouns in a clause is predictable, typically depending on the complexity of the pronominal phrase and the speaker’s communicative intentions.
Keywords: corpus analysis; epistemic indefinite pronouns; epistemični nedoločni zaimki; implicational map for indefinite pronoun functions; implikacijski zemljevid funkcij nedoločnih zaimkov; k negativni polarnosti usmerjeni izrazi; korpusna analiza; Negative Polarity Items; poljubnostni zaimki; Slovene bare pronouns